Challenges and strategies in feeding AI-powered translation machine with religious texts: English department students’ experiences - Adaninggar Septi Subekti; Kurniawati, Lemmuela Alvita; Wati, Mega (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Religious texts contain unique linguistic, cultural, and interpretive challenges, such as sacred terms, figurative language, context-bound meanings, and doctrinal sensitivity. It delves explicitly into the participants’ challenges and strategies to navigate the process. The present study aims to explore Indonesian English department students’ experiences in feeding an Artificial Intelligence (AI)-powered translation platform with the English translation of Indonesian religious texts. The study employed qualitative secondary document analysis of the reflections of six students, who consented to their reflections being used for this study. Thematic Analysis was employed to fulfill the research objectives. This study found that students had difficulty capturing subtle meanings, implied messages, and contextual interpretations in the texts when translating the texts due to their lack of knowledge about the cultural aspects of the translated texts. This study further revealed that to navigate the process of feeding the platform, the students employed three strategies. They consulted with the peer translators and the teachers, used other AI tools to improve the quality of the translation, and self-regulated themselves in response to the demanded quality of the translation. Accordingly, this study provides insights into the complex behind-the-scenes dynamics of AI-powered translation feeding and how these dynamics can support students’ translation learning.